Bali Cattle Business Competitiveness According to the Moyo Watershed (DAS) in Sumbawa Regency, West Nusa Tenggara - Ahmad Yani; Cecep Budiman; Amrullah; Sukarne (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The research objectives were: (1) to analyze the cost of domestic resources for Bali cattle according to the business typology and (2) to analyze the efficiency of the Bali cattle business according to the business typology. The research location was the central area of the Moyo Watershed, Sumbawa Regency, with 50 random respondents and key figures: village heads, heads of livestock groups, intermediary traders, inter-island wholesalers, traders of agricultural tools, materials and medicines as well as the livestock and animal health services of Sumbawa Regency. Methods of taking respondents randomly based on business typology with survey methods and analyzed by (1) domestic resource cost analysis (BSD) and (2) Policy Analysis Matrix (PAM) analysis. From the results of the study, information was obtained that bali cattle breeders in the central area of the Moyo Watershed, Sumbawa Regency, West Nusa Tenggara used 3 (three) business typologies, namely: (1) breeding business typology, (2) savings business typology and (3) combination business typology (1+2). Comparative competitiveness of Bali cattle according to business typology as shown by the respective DRCR values, namely breeding typology 0.54; savings typology 0.49 and combination typology 0.32. The competitive competitiveness shown by the PCR value is the breeding typology of 0.49; savings typology 0.59 and combination typology 0.35.